Two Years Before the Mast - Dana, Richard Henry, 1815-1882; Keyes, Homer Eaton, 1875-1938 (Salt Lake City, UT : Project Gutenberg, 2000)
"Two Years Before the Mast" by Richard Henry Dana Jr. is a memoir published in 1840, recounting his 1834-1836 voyage as a common sailor from Boston to California. Dana vividly chronicles life at sea aboard a merchant brig trading for cow hides along the Mexican California coast. He describes navigating Cape Horn's treacherous winter storms, witnessing brutal floggings by his captain, befriending Hawaiian sailors, and observing early California settlements. This groundbreaking account exposed the harsh realities of maritime life and advocated for seamen's rights. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Two_Years_Before_the_Mast
See also PG#4277 with Introduction and afterword by Richard Henry Dana III
Release date is 2000-02-01
Produced by Robert E. Brewer. HTML version by Al Haines.
Keywords: Seafaring life; Dana, Richard Henry, 1815-1882; Voyages and travels; Sailors